(3aQGFO GdahGFO aj GdefWb Ch ahGFO GdefWbjIs - (3ejQRG ZdGe Ydi Hf eMeO Hf YHO GdcQje GdgQhj GdMGFQjs ((3GdeDdas)
(3ChdgG (B:s
(3dc GdMeO jGPG GdLhO (B... (3gPg ahGFO dWjaI haQGFO TQjaI dEjVGM HYV GdeSGFd GdefWbjI heG jJYdb HgG cJHJgG SHHG dPcQi hCOGA dTcQi aCNPgG eJe dfHd GdWGdHjf hfjdgG ege ddeHJOFjf (B...s
(3BNQgG (B:s
.. (3heOGQ GdTYQ Ydi GdCcGPjH hbGd GddY JYGdi (B{ (3heG YdefGg GdTYQ heG jfHZj dg (B} (3hCMSf ef aUd GdcdGe aj gPg GdUfGYGJ GdeMbb GdWhSj hEf cGf GdJaUjd ajgG jNQL GdcdGe Yf Gdaf CYfj GdefWb (B.s
(3HChdg agQS , hCNQgG Ydjg JbQjXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B16\333s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs